PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL KELAS VIII DI MTS AL-KHOLIDIYAH SEDINGINAN KABUPATEN ROKAN HILIR - Dewi Agustina; Makhdalena '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: The learning model of Two Stay Two Stray technique or method two only two guests. Learning is a learning models that begins with the division of the group, and provide opportunities for groups to share results and information. The purpose of this study is to Determine the Increase in student motivation on the subjects of social sciences through a learning model of Two Stay Two Stray (TSTS) Class VIII at MTs Al-Kholidiyah Sedinginan Rokan Hilir. Place of research conducted at MTs Al-Kholidiyah Sedinginan Rokan Hilir class. The sample used is a class VIII student number 32, composed of 20 women and 12 men. Data Obtained using techniques obserpasi and observation for two weeks. While the data analysis techniques used are: analysis of the activity of teachers and students and the analysis of the motivation to learn. From the results of the data analysis that has been done shows. application of learning models Two Stay Two Stray (TSTS) can Increase students' motivation on the subjects of Social Sciences Class VIII at MTs Al-Kholidiyah Sedinginan Rokan Hilir. From Reviews These results it is expected that the teacher suggested MTs Al-Kholidiyah Sedinginan, learning TSTS can use as an alternative model of learning to improve students' motivation. However, this method should be Able to use the time as possible.Keywords: PPD Learning Method , Motivation